The influence of service quality and corporate image on students' loyalty in higher education - Zainudin Awang (Fakulti Pengurusan Ekonomi, 2011)
Today, postgraduate education has become an important commodity in higher education industry and the competition for postgraduate customers among universities is stiff. As of 2006, there are 20 public universities, 21 private universities and more than 500 colleges in Malaysia competing for postgraduate students, their paying customers. The number of private institutions has increased tremendously after the government allowed private organizations to set-up their own universities and colleges. Furthermore, the government also allows foreign universities to market their programs in the country and even to set up their branch campuses here.